Upaya Meningkatkan Hasil Belajar IPS Menggunakan Model Direct Instruction dengan Media Animasi pada SDS Muhammadiyah Selat Kelas Iv-A Tahun Pelajaran 2016/2017 - Novi Maulana Hakim; Muhamad Ramli (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2019)
This study aims to (1) describe the learning activities of students in teaching and learning activities using the Direct Instruction Model with Animation Media (2) to know the increase in social studies learning outcomes at SDS Muhammadiyah Strait of Class IVA after using the Direct Instruction Model with Animation Media. The type of research used by researchers is to use a class action research design (CAR) that seeks to solve problems faced in the current situation. With the number of research subjects 27 students namely 16 men and 11 women — qualitative and quantitative data analysis techniques. The results of the study show that: (1) Student learning activities are good at social studies learning using Direct Instruction models with animated media. The first cycle of student activity has an average value of 3.52 with good categories and the second cycle of student activity has an average value of 3.94 in the excellent class. (2) There is an increase in learning outcomes after learning by using the Direct Instruction model with animation media on social studies lessons for students of class IVA SDS Muhammadiyah Selat. This can be seen from the data on student learning outcomes. In the initial test of learning outcomes students get 48% classical completeness with an average value of 61, in the first cycle the learning outcomes of students get 77% artistic completeness with an average value of 70 and in the second cycle the learning outcomes of students get 100% classical completeness with an average amount of 87 reaching the specified KKM.